Radiation recall dermatitis following adjuvant capecitabine in breast cancer: A case report (Indian Journal of Case Reports, 2024)
Radiation recall dermatitis (RRD) is an acute inflammation of the skin, i.e., produced by drugs, most commonly chemotherapeutic treatments, in an area of the body that has been treated with radiation in the past. This case report describes the clinical experience of a triple-negative breast cancer patient who developed RRD after postoperative radiotherapy following adjuvant capecitabine treatment. The timing of chemotherapy after radiation therapy and the improvement in radiation dermatitis following capecitabine avoidance suggest that the reaction was a true radiation recall phenomenon.